Surface Modification of Li1.2Mn0.56Ni0.16Co0.08O2 Cathode Material by Supercritical CO2 for Lithium-Ion Batteries. Issue 11 (7th September 2018) - Ji, Yuanpeng; Li, Ruhong; Mu, Deying; Sun, Shuting; Dai, Changsong; Ding, Fei
Abstract : Feasible surface modification of lithium-rich Li1.2 Mn0.56 Ni0.16 Co0.08 O2 cathode material is provided by supercritical CO2 to introduce oxygen vacancies on the surface of material particles. Through the characterization of X-ray diffraction, X-ray photoelectron spectroscopy, X-ray absorption spectroscopy, scanning electron microscopy and transmission electron microscopy, the results demonstrate that oxygen vacancies successfully form under the scour of supercritical CO2, while the inner structure remains integrity. In the electrochemical experiments, compared with the pristine samples, surface-modified material (marked as SC-LLMO) exhibits higher initial coulombic efficiency and more outstanding rate capability. The initial coulombic efficiency raises from 75.97% for pristine cathode to 82.24% for SC-LLMO cathode at the current density of 12.5 mA g −1, which can be attributed to the effect of pre-activation of the Li2 MnO3 component, leading an increase in the content of trivalent manganese and reversible oxygen. The existence of oxygen vacancies, expanded unit cell volume and a larger amount of trivalent manganese provide an environment conducive to lithium ion migration, which are the main reasons for better rate performance.